A Si–MnOOH composite with superior lithium storage properties. Issue 28 (9th March 2015) - Zhong, Hai; Yang, Yanbo; Ding, Fei; Wang, Donghai; Zhou, Yunhong; Zhan, Hui
Abstract : The Si–MnOOH composite electrode shows excellent rate capability, which can be attributed to the γ-MnOOH component that significantly promotes the catalyzing effect. Abstract : The Si–MnOOH composite electrode exhibits very stable cycling and excellent rate capability, such as 1200 mA h g −1 at 12 A g −1, and 700 mA h g −1 at 20 A g −1 . The γ-MnOOH component significantly promotes the alloying/de-alloying reaction between Si and lithium.